2006
DOI: 10.1002/anie.200503314
|View full text |Cite
|
Sign up to set email alerts
|

Elementary Arithmetic Operations by Enzymes: A Model for Metabolic Pathway Based Computing

Abstract: Physio‐logical: A system of four enzymes, horseradish peroxidase, glucose dehydrogenase, glucose oxidase, and catalase, operate in parallel in the presence of NADH and NAD+ to yield AND and XOR gates (see picture). Glucose and H2O2 act as the inputs, and the absorbance that follows the production of gluconic acid or NADH provide the outputs of the AND and XOR gates, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
135
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(140 citation statements)
references
References 32 publications
0
135
0
3
Order By: Relevance
“…The information processing and storing "units" need not be limited to molecules. They can include [1][2][3][4][5][6][7][8][9][10][11][12][13] natural and synthetic supra-molecular, biomolecular and/or catalytic structures (enzymes, DNA, etc. ), as well as whole cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The information processing and storing "units" need not be limited to molecules. They can include [1][2][3][4][5][6][7][8][9][10][11][12][13] natural and synthetic supra-molecular, biomolecular and/or catalytic structures (enzymes, DNA, etc. ), as well as whole cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the biocatalytic nature of many utilized biomolecular processes, offers certain advantages for analog noise control in the binary-gate circuit design paradigm. [17] Proteins/enzymes [5][6][7][8][9][10][11][12][14][15][16][17][19][20][161][162][163][164][165] and DNA/RNA/DNAzymes [6,7,[166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181][182] have been extensively used for gates, for realizing small networks and computational units, and for systems motivated [183] by applications.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] In parallel, several groups have shown that it is possible realize complex combinational logic circuits at the molecular scale, up to half and full addition or subtraction using various external perturbations, i.e., chemical, biochemical, photochemical, optical, electrochemical, electrical, to address the system, encode the inputs and perform the logic operations. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] We propose here another approach for implementing molecular logic gates.…”
Section: Introductionmentioning
confidence: 99%
“…It is impossible to overestimate the scientific and practical importance of this research and engineering for basic science and for practical use in medicine, high-tech industry, military and homeland security applications. Also, the bioelectronic systems could be further developed for biocomputing applications [10]. This area of bioelectronics is still in its infancy.…”
Section: Eugenii Katz Guest Editormentioning
confidence: 99%